TATA KELOLA PERUSAHAAN DAN STRUKTUR MODAL DENGAN ARUS KAS OPERASI SEBAGAI INTERVENING - Budiman, Johny (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
This study aims to determine the direct and indirect effect of corporate governance on the capital structure with cash flow from operation as an intervening variable. Independent variables used in this research are board size, audit committe, independen audit committe, audit committe expertiseâ in finance, audit committe meetings, board commisioner composition and institutional ownership. Â The capital structure is measured by the debt ratio. Samples from this study were 65manufacturing firms sub sector basic industries and chemicals listed on the Indonesia Stock Exchange and were selected using purposive sampling method. Data have been obtained will be tested with path analysis. The results of this study indicate that there were direct and negative significant influence of audit committe, and positive significant of audit committe meeting and board of commisioner composition on capital structure. The results also showed that there were indirect effect and significant of board size and audit commitee espertiseâ in finance on capital struture with cash flow operation as an intervening variable.